The diagnosis and treatment of invasive aspergillosis in Dutch haematology units facing a rapidly increasing prevalence of azole‐resistance. A nationwide survey and rationale for the DB‐MSG 002 study protocol. Issue 9 (13th July 2018) - Schauwvlieghe, Alexander F. A. D.; de Jonge, Nick; van Dijk, Karin; Verweij, Paul E.; Brüggemann, Roger J.; Biemond, Bart J.; Bart, Aldert; von dem Borne, Peter A.; Verbon, Annelies; van der Beek, Martha T.; Demandt, Astrid M. P.; Oudhuis, Guy J.; et al.
Summary: Patients with haematological malignancies are at risk for invasive fungal diseases (IFD). A survey was conducted in all Dutch academic haematology centres on their current diagnostic, prophylactic and therapeutic approach towards IFD in the context of azole‐resistance. In all 8 centres, a haematologist and microbiologist filled in the questionnaire that focused on different subgroups of haematology patients. Fungal prophylaxis during neutropaenia was directed against Candida and consisted of fluconazole and/or amphotericin B suspension. Mould‐active prophylaxis was given to acute myeloid leukaemia patients during chemotherapy in 2 of 8 centres. All centres used azole prophylaxis in a subset of patients with graft‐versus‐host disease. A uniform approach towards the diagnosis and treatment of IFD and in particular azole‐resistant Aspergillus fumigatus was lacking. In 2017, all centres agreed to implement a uniform diagnostic and treatment algorithm regarding invasive aspergillosis with a central role for comprehensive diagnostics and PCR‐based detection of azole‐resistance. This study (DB‐MSG 002) will re‐evaluate this algorithm when 280 patients have been treated. A heterogeneous approach towards antifungal prophylaxis, diagnosis and treatment was apparent in the Netherlands. Facing triazole‐resistance, consensus was reached on the implementation of a uniform diagnostic approach in all 8 centres.